Prevalence and genetic variability of occult hepatitis B virus in a human immunodeficiency virus positive patient cohort in Gondar, Ethiopia - Patel, Nishi H.; Meier-Stephenson, Vanessa; Genetu, Meaza; Damtie, Debasu; Abate, Ebba; Alemu, Shitaye; Aleka, Yetework; Van Marle, Guido; Fonseca, Kevin; Coffin, Carla S.; Deressa, Tekalign (PloS one, 2020)
Occult hepatitis B (OHB) is a major concern in HIV infected patients as it associates with a high risk of HBV reactivation and disease progression. However, data on the prevalence of OHB among HIV positive patients in Ethiopia is lacking. This study aims to determine the prevalence of OHB in HBV/HIV co-infected patients from Gondar, Ethiopia. A total of 308 consented HIV positive patients were recruited from the University of Gondar Teaching Hospital, Ethiopia. Clinical and demographic data of the participants were recorded. Plasma was tested for HBsAg and anti-HBc using commercial assays (Abbott Architect). In HBsAg negative anti-HBc positive patient samples, total DNA was isolated and amplified using nested PCR with primers specific to HBV polymerase, surface and pre-core/core regions, followed by Sanger sequencing and HBV mutational analysis using MEGA 7.0. Of the total study subjects, 62.7% were female, median age 38.4 years, interquartile range (IQR): 18-68, and 208 (67.5%) had lifestyle risk factors for HBV acquisition. Two hundred and ninety-one study subjects were HIV+/HBsAg-, out of which 115 (39.5%) were positive for anti-HBc. Occult hepatitis B was detected in 19.1% (22/115) of anti-HBc positive HIV patients. HBV genotype D was the predominant genotype (81%) among OHB positive patients. Mutations associated with HBV drug resistance, HBV reactivation, and HCC risk were detected in 23% (5/22), 14% (3/22) and 45.5% (10/22) of patients, respectively. This study found a high rate of occult hepatitis B in HIV patients. Further, high rates of mutations associated with HBV reactivation, drug resistance, and HCC risk were detected in these patients. These data highlighted the need for integrating OHB screening for proper management of liver diseases in HIV patients.